A Novel Strategy Conjugating PD-L1 Polypeptide With Doxorubicin Alleviates Chemotherapeutic Resistance and Enhances Immune Response in Colon Cancer - Wang, Maolin; Shu, Xing-sheng; Li, Meiqi; Zhang, Yilin; Yao, Youli; Huang, Xiaoyan; Li, Jianna; Wei, Pengfei; He, Zhendan; Lu, Jun; Ying, Ying (Frontiers in Oncology, 2021)
Abstract Background: Modifying the structure of anti-tumor chemotherapy drug is of significance to enhance the specificity and efficacy of drug-delivery. A novel proteolysis resistant PD-L1-targeted peptide (PPA1) has been reported to bind to PD-L1 and disrupt the PD-1/PD-L1 interaction, thus appearing as an outstanding tumor-targeting modification of synergistic drug conjugate for effective anti-tumor treatment. However, the combination regimen of coupling PD-L1 polypeptide with chemotherapeutic drug in tumoricidal treatment has not been reported thus far. Methods: We developed a novel synergistic strategy by conjugating PPA1 to doxorubicin (DOX) with a pH sensitive linker that can trigger the release of DOX near acidic tumor tissues. The binding affinity of PPA1-DOX with PD-L1 and the acid-sensitive cleavage of PPA1-DOX were investigated. A mouse xenograft model of colon cancer was used to evaluate the biodistribution, cytotoxicity and anti-tumor activity of PPA1-DOX. Results: PPA1-DOX construct showed high binding affinity with PD-L1 in vitro and specifically enriched within tumor when administered in vivo. PPA1-DOX exhibited a significantly lower toxicity and a remarkably higher antitumor activity in vivo, as compared with free PPA1, random polypeptide-DOX conjugate, DOX, or 5-FU, respectively. Moreover, increased infiltration of both CD4+ and CD8+ T cells was found in tumors from PPA1-DOX treated mice. Conclusions: We describe here for the first time that the dual-functional conjugate PPA1-DOX, which consist of the PD-L1-targeted polypeptide that renders both the tumor-specific drug delivery and inhibitory PD-1/PD-L1 immune checkpoint inhibition, and a cytotoxic agent that is released and kills tumor cells once reaching tumor tissues, thus representing a promising therapeutic option for colon cancer with improved efficacy and reduced toxicity.